3D Reconstruction in Ocean Environment Combining Photography with Subsea Positioning Sensors - Buchanan, Alan (Curtin University, 2021)
This research involves 3D reconstruction from photography in a subsea environment. Recent developments in photogrammetric processing and digital camera technology provides an opportunity to provide an alternative to more traditional subsea techniques.for subsea surveying. This research opens a new field in subsea mapping. The ability to produce mapping products without requiring any extra equipment will be very attractive to industry.